Development of soybeans with low P34 allergen protein concentration for reduced allergenicity of soy foods. (4th July 2016) - Watanabe, Daisuke; Adányi, Nóra; Takács, Krisztina; Maczó, Anita; Nagy, András; Gelencsér, Éva; Pachner, Martin; Lauter, Kathrin; Baumgartner, Sabine; Vollmann, Johann
Abstract: BACKGROUND: In soybean, at least 16 seed proteins have been identified as causing allergenic reactions in sensitive individuals. As a soybean genebank accession low in the immunodominant protein P34 (Gly m Bd 30K) has recently been found, introgression of the low‐P34 trait into adapted soybean germplasm has been attempted in order to improve the safety of food products containing soybean protein. Therefore, marker‐assisted selection and proteomics were applied to identify and characterize low‐P34 soybeans. RESULTS: In low‐P34 lines selected from a cross‐population, concentrations of the P34 protein as identified with a polyclonal antibody were reduced by 50–70% as compared to P34‐containing controls. Using 2D electrophoresis and immunoblotting, the reduction of P34 protein was verified in low‐P34 lines. This result was confirmed by liquid chromatographic–tandem mass spectrometric analysis, which revealed either a reduction or complete absence of the authentic P34 protein as suggested from presence or absence of a unique peptide useful for discriminating between conventional and low‐P34 lines. CONCLUSION: Marker‐assisted selection proved useful for identifying low‐P34 soybean lines for the development of hypoallergenic soy foods. The status of the P34 protein in low‐P34 lines needs further characterization. In addition, the food safety relevance of low‐P34 soybeans should be tested in clinical studies. © 2016 Society of Chemical Industry